FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS HASIL PEMERIKSAAN KEUANGAN NEGARA (Studi Kasus pada BPK RI Perwakilan Prov. Kepulauan Bangka Belitung) - Ivan Juniansyah; Nurul Fachriyah (Jurnal Ilmiah Mahasiswa FEB, 2014)
The purpose of this study is to determine the effect of training, experience, gender, age, and educational background of auditors to the quality of state financial audit. This study used 60 sample of auditors at Bangka  Belitung Provincial Representative office with purposive sampling method. The method of analyzing data used is multiple linier regresion.        The result of the study showed that from the five variables that determine the quality of state financial audit result, only two variables that affect  the quality of state financial audit result. The two variables are training and experience.While gender, age and educational background doesn’t affect the quality of state financial audit result.Keyword : The quality of audit results, Training, Experience, Gender, Age, dan Educational Background.